The Equine Gingiva: A Gross Anatomical Evaluation - Steinfort, Saskia; Obach-Schröck, Carmen; Röcken, Michael; Theiss, Felix; Failing, Klaus; Vogelsberg, Jörg; Staszyk, Carsten (Frontiers in Veterinary Science, 2019)
Equine periodontal disease (ePD) usually starts with gingival inflammation, which proceeds towards the periodontal space, causing detachment of tooth supporting periodontal fibres. Although several therapeutical procedures have been proposed, ePD is often only diagnosed in advanced stages, requiring dental extraction. A similar dilemma has been observed in small animal medicine, but has been overcome by the introduction of reliable examination protocols for the early diagnosis of periodontal diseases (PD). These protocols are based on detailed anatomical descriptions of healthy gingiva, allowing for the determination of the pathognomonic signs of the onset of PD and providing a basis for grading systems and treatment plans. Consequently, proposals have also been made for periodontal examination protocols in horses. However, these protocols were widely adopted from small animal medicine assuming a similar anatomy of the equine and canine gingiva. To provide a solid anatomical basis for equine specific periodontal examinations, 20 equine heads were examined macroscopically, with special attention to the gingival sulcus, the gingival margin and the interdental papillae. Constant morphological patterns of the gingival margin and the interdental papillae were found for the vestibular and lingual/palatal aspects of the upper and lower cheek tooth arcades, as well as for the incisor arcades. A gingival sulcus measuring greater than 1 mm was present in only 6% of the investigated specimens. The inspection of the gingival margin and the interdental papillae, as well as the recognition of a gingival sulcus, may serve as criteria to establish equine specific periodontal investigation protocols.